Employing modern technology in developing Iraqi political awareness under the new government Facebook as a model An analytical study for the period from 27/10/2022 to 27/11/2022 - Fatima Mahmoud Hama , Researcher (lark, 2023)
This research aims to know the function of modern technology and the mechanism of employing it for political awareness topics represented by the page of (Media Office of the Iraqi Prime Minister) on Facebook. The survey descriptive method was used in the method of analysing the content to study and analyse the published topics for the period from 27/10/2022 to 27/11/2022, which number (183) topics to reach the research objectives that answer the question of the research problem. Among the most important findings of a study in this research are: One of the most important topics dealt with by the page (Media Office of the Iraqi Prime Minister) in this research are the topics (political, security, economic, social), all of which are part of political awareness, because the failure or neglect of the new government in any of these fields creates political crises in the country. The contents of the arts that dealt with political awareness stressed that eliminating financial and administrative corruption, eliminating poverty and unemployment and reducing family problems are among the most important focusses on the new government. The page presented the topics of awareness through the art of press news, which is the most important journalistic arts, then the press conference and the press report The page highlighted the topics by publishing the news attached to pictures as well as using videos and infographs. Views recorded the highest percentage of the extent of interaction with the topics presented in the way of videos, followed by likes, then comments and finally participation.